Comparative political economy : the resource curse. (SAGE video tutorials., 2016)
Chungshik Moon defines resource curse as a negative effect of a natural resource on the economic, social, or political well-being of a community. This effect can be explained by two factors: deindustrialization and/or low government accountability.